Assessment of pure, mixed and diluted deep eutectic solvents on Napier grass (Cenchrus purpureus): Compositional and characterization studies of cellulose, hemicellulose and lignin. (15th April 2023) - Gundupalli, Marttin Paulraj; Cheenkachorn, Kraipat; Chuetor, Santi; Kirdponpattara, Suchata; Gundupalli, Sathish Paulraj; Show, Pau-Loke; Sriariyanun, Malinee
Abstract: Pretreatment with pure, mixed, and diluted deep eutectic solvents (DESs) was evaluated for its effect on Napier grass through compositional and characterization studies. The morphological changes of biomass caused by pretreatment were analyzed by FTIR and XRD. The cellulose and hemicellulose content after pretreatment using mixed DES increased and decreased 1.29- and 4.25-fold, respectively, when compared to untreated Napier grass. The crystallinity index (CrI. %) of mixed DES sample increased due to the maximum removal of hemicellulose (76 %) and delignification of 62 %. The material costs of ChCl/FA and ChCl/LA for a single run are ≈2.16 USD and ≈1.65 USD, respectively. Pure DES showed that ChCl/LA pretreatment enhanced delignification efficiency and that ChCl/FA increased hemicellulose removal. It was estimated that a single run using ChCl/LA:ChCl/FA to achieve maximum hemicellulose and lignin removal would cost approximately ≈1.89 USD. Future work will evaluate the effect of DES mixture on enzyme digestibility and ethanol production from Napier grass. Hypotheses: Deep eutectic solvent (DES) pretreatment studies on the fractionation of lignocellulosic biomass have grown exponentially. The use of pure and diluted DES has been reported to improve saccharification efficiency, delignification, and cellulose retention (Gundupalli et al., 2022). These studies have reported maximum lignin removal but also a lower effect on hemicellulose removal from lignocellulosic biomass. It was hypothesized that mixing two pure DESs could result in maximum removal of hemicellulose and lignin after pretreatment. To our knowledge, no studies have been performed to investigate the efficiency of pretreatment using a DES mixture and compared the outcome with pure and diluted DESs. Furthermore, it was hypothesized that using two pure DESs in a mixed form could lower the material cost for each experimental run. Process efficiency was determined by compositional, XRD, and FTIR analysis. Avenues for future research include determining glucose and ethanol yields during the enzymatic saccharification and fermentation processes. Graphical abstract: Unlabelled Image